Peningkatan Kemampuan Konsep Dasar Matematika Siswa Melalui Program Bimbingan Belajar LIMA: Latihan Intensif Matematika Asyik - Wahyuni; Yunita Maharani; Ahmad Nur; Ummu Kalsum; Nurul Aisyah J; Arini Muhlisa (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
This community service program aims to strengthen students’ understanding of basic mathematical concepts through the LIMA (Latihan Intensif Matematika Asyik) tutoring program at SMPN 3 Majene. The implementation of the program was motivated by students’ low conceptual mastery, particularly in integer operations, which hindered their learning progress. The activities were carried out in three stages: preparation through observation and socialization, implementation using the LIMA Module that provides structured exercises and intensive assistance, and evaluation through the “hiking evaluation” method designed to be more interactive and engaging. The results showed improvements in students’ conceptual understanding, confidence in asking questions, and learning motivation. Overall, the LIMA program proved effective in enhancing students’ mathematical comprehension and can serve as a relevant supplementary mentoring model for strengthening basic concepts in schools.